Wind modulation of upwelling at the shelf-break front off Patagonia: Observational evidence - Carranza, Magdalena (2017)
The South-Atlantic Patagonian shelf is the largest chlorophyll-a (Chl-a) hot spot in Southern Ocean color images. While a persistent 1500 km long band of high Chl-a along the shelf-break front (SBF) is indicative of upwelling, the mechanisms that drive it are not entirely known. Along-front wind oscillations can enhance upwelling and provide a nutrient pumping mechanism at shelf-break fronts of western boundary currents. Here we assess wind-induced upwelling at the SBF off Patagonia from daily satellite Chl-a and winds, historical hydrographic observations, cross-shelf Chl-a fluorescence transects from two cruises, and in situ winds and water column structure from a mooring site. Satellite Chl-a composites segregated by along-front wind direction indicate that surface Chl-a is enhanced at the SBF with southerly winds and suppressed with northerly winds. Northerly winds also result in enhanced Chl-a further offshore (∼25–50 km). Synoptic transects as well as mean hydrographic sections segregated by along-front winds show isopycnals tilted upward for southerly winds. Spring observations from the mooring also suggest that southerly winds destratify the water column and northerly winds restratify, in agreement with Ekman transport interacting with the front. Moreover, changes in water column temperature lag along-front wind forcing by 2–4 days. Our results suggest that oscillations in along-front winds, on timescales typical of atmospheric storms (2–10 days), can significantly modulate the upwelling and Chl-a concentrations at the SBF off Patagonia, revealing the importance of wind-induced upwelling for shelf-slope exchange at shelf-break fronts of western boundary currents.